Profiling high-growth enterprises in Portugal - Sarmento, Elsa (2014)
This paper describes employer enterprise dynamics in Portugal for high-growth and gazelle enterprises for the period 1990-2007, using the methodology by Eurostat/OECD. It discusses stylized facts related to performance and employment by size, region and sector, to a detail which has not been previously considered, uncovering potential business areas of growth which are of prime importance for the country’s economic growth and development. Two parallel perspectives are provided, by turnover and by employment. We also provide a comparison between Portuguese firms and some of their European counterparts. This contrast highlights differences in performance related to underlying national framework conditions, and specifically to the regulatory and cultural environment in which Portuguese firms operate, which seems to be instrumental to the understanding of their poorer performance.